2, 3, 5, 4′‐Tetrahydroxystilbene‐2‐O‐β‐d‐glucoside eliminates ischemia/reperfusion injury–induced H9c2 cardiomyocytes apoptosis involving in Bcl‐2, Bax, caspase‐3, and Akt activation. Issue 7 (19th March 2019) - Sun, Tao; Liu, Han; Cheng, Yutong; Yan, Lixiao; Krittanawong, Chayakrit; Li, Shihong; Qian, Wang; Su, Wang; Chen, Xuanzu; Hou, Xuejian; Zhang, Hongju
Abstract: Objective: This study was designed to explore the protective effect of 2, 3, 5, 4′‐tetrahydroxystilbene‐2‐O‐β‐d ‐glucoside (TSG) against ischemia/reperfusion (I/R) injury–induced cardiomyocytes apoptosis. Methods: The H9c2 cell I/R injury model was induced by simultaneous shortage of nutrients and oxygen. TSG administration (0.10, 0.25, and 0.50 mM) was performed before and during I/R stimulation. Cell apoptosis was evaluated using terminal deoxynucleotidyl transferase dUTP nick end labeling assay. Expression of cell‐related proteins was detected to assess the effect of TSG on cell apoptosis. Results: I/R injury induced significant cell apoptosis. Significantly decreased Bcl‐2 and increased Bax, caspase‐3, and p‐Akt expression ( P < 0.01) was detected in the cell model of I/R injury. In contrast, TSG administration eliminated all the changes induced by I/R injury in a dose‐dependent manner. Compared with the H9c2 cell model of I/R injury, the H9c2 cells treated with 0.50 mM TSG showed the lowest cell apoptosis percentage, the highest expression of Bcl‐2, and the lowest expression of Bax, caspase‐3, and p‐Akt ( P < 0.01). Conclusion: We confirmed that the protective effect of TSG against I/R injury–induced cell apoptosis in H9c2 in vitro was associated with the Bcl‐2/Bax ratio, caspase‐3, and Akt activation. Abstract : We confirmed that the protective effect of 2, 3, 5, 4′‐tetrahydroxystilbene‐2‐O‐β‐d ‐glucoside (TSG) against ischemia/reperfusion (I/R) injury–induced cell apoptosis in H9c2 in vitro was associated with the Bcl‐2/Bax ratio, caspase‐3, and Akt activation.